Post-stroke cognitive impairment and synaptic plasticity: A review about the mechanisms and Chinese herbal drugs strategies - Chi, Xiansu; Wang, Liuding; Liu, Hongxi; Zhang, Yunling; Shen, Wei (Frontiers in Neuroscience, 2023)
Post-stroke cognitive impairment, is a major complication of stroke, characterized by cognitive dysfunction, which directly affects the quality of life. Post-stroke cognitive impairment highlights the causal relationship between stroke and cognitive impairment. The pathological damage of stroke, including the increased release of excitatory amino acids, oxidative stress, inflammatory responses, apoptosis, changed neurotrophic factor levels and gene expression, influence synaptic plasticity. Synaptic plasticity refers to the activity-dependent changes in the strength of synaptic connections and efficiency of synaptic transmission at preexisting synapses and can be divided into structural synaptic plasticity and functional synaptic plasticity. Changes in synaptic plasticity have been proven to play important roles in the occurrence and treatment of post-stroke cognitive impairment. Evidence has indicated that Chinese herbal drugs have effect of treating post-stroke cognitive impairment. In this review, we overview the influence of pathological damage of stroke on synaptic plasticity, analyze the changes of synaptic plasticity in post-stroke cognitive impairment, and summarize the commonly used Chinese herbal drugs whose active ingredient or extracts can regulate synaptic plasticity. This review will summarize the relationship between post-stroke cognitive impairment and synaptic plasticity, provide new ideas for future exploration of the mechanism of post-stroke cognitive impairment, compile evidence of applying Chinese herbal drugs to treat post-stroke cognitive impairment and lay a foundation for the development of novel formulas for treating post-stroke cognitive impairment.